Analysis of Slaughterhouses' Legal Awareness of Halal Certification Standards from the Perspective of Law Number 33 of 2014 Concerning Halal Product Assurance in Binjai City - Amanda Pramudita; Muhammad Nur Iqbal (Dinasti Research, 2025)
With the advancement of science and technology today, there are new concerns about product quality in terms of halal certification. For example, the ethics of chicken slaughter are often questioned and doubted along with various slaughtering methods, resulting in various slaughter models. Some are done traditionally, and others are made with machines. However, many people are unaware of the standards of animal slaughter and processing, and not many people are aware of the importance of obtaining halal certification. The purpose of this study is to determine how to analyze the legal awareness of slaughterhouses in Binjai City regarding halal certification standards from the perspective of Law No. 33 of 2014 concerning Halal Product Assurance. To determine efforts that can be made to increase legal awareness of slaughterhouse managers regarding the obligation of halal certification in Binjai City. The research method used a qualitative approach with field research. Data were collected through observation, interviews, and documentation with slaughterhouse operators and related parties. Then, descriptive analysis was carried out with reference to the theory of legal compliance and halal certification regulations in Indonesia. The results of this study indicate that. The level of legal understanding of slaughterhouse operators in Binjai City regarding the obligation to obtain halal certification based on the Perspective of Law Number 33 of 2014 concerning Halal Product Assurance is still low. This is evident from the fact that, although legal knowledge about halal certification is quite high, they do not understand the regulations related to halal certification, resulting in their inability to understand it properly. Efforts to improve compliance of slaughterhouse operators in Binjai City with halal certification are carried out through scheduled socialization and training, systematic data collection, technical assistance, and the development of a digital monitoring system. The active role of the local government as a facilitator and coordinator with the certification body is very important, accompanied by regular monitoring. This integrated approach encourages slaughterhouse operators to comply, increases consumer trust, and product competitiveness in local and national markets.